Color Card Sebagai Media Pembelajaran Pengkajian Luka Infeksi - Nur Asmi Sulasri; Ivony FN Putriningtyas; Reflin Msen (Universitas Malahayati Lampung, 2022)
ABSTRACT: COLOR CARD AS A LEARNING MEDIA FOR THE ASSESSMENT OF INFECTIONS Backround: The color card is one of the supporting media for skill learning that can support the clinical skills of nursing students in treating infectious wounds. Purpose: This study aims to prove the effectiveness of color card s in improving student skills in the assessment of infectious wounds in the laboratory. Method: Experimental research with randomized kontrol trial design on 30 final year Nursing Diploma III students who were selected using a consecutive sampling technique and divided into 2 groups. The experimental group (n=15) used learning using color card s, while the kontrol group (n=15) used conventional wound assessment lessons. We assessed wound assessment skills before and 6 days after the intervention using a standard operating procedure (SOP) for wound assessment, color card s, Battes Jensen wound assessment form, and infectious wound manikins. Data analysis used paired t-test and N-gain score test. Result: The results of the paired t-test showed a statistically significant difference in skill improvement in the two groups (p=0.000). However, the average increase (mean) showed that the intervention group had a higher difference value (61.2000 to 90.800) than the kontrol group (59.1333 to 69.9333). Using color card media was able to increase the sample skills up to 76.96% compared to the conventional method, which was only 26.08%. Conclusion: It can be concluded that the use of color card media is effective for improving the sample's skills in assessing infectious wounds. Keywords: color card ; skill lab; laboratory; nursing; wound care INTISARI: COLOR CARD SEBAGAI MEDIA PEMBELAJARAN PENGKAJIAN LUKA INFEKSI Pendahuluan: Color card merupakan salah satu media pendukung pembelajaran praktikum yang dapat mendukung keterampilan klinis mahasiswa keperawatan dalam melakukan perawatan luka infeksi.Tujuan: Penelitian ini bertujuan untuk membuktikan efektifitas color card dalam meningkatkan keterampilan mahasiswa dalam pengkajian luka infeksi di laboratorium.Metode: Penelitian eksperimental dengan design randomized kontrol trial pada 30 mahasiswa diploma III Keperawatan tingkat akhir yang dipilih menggunakan teknik consecutive sampling dan dibagi menjadi 2 kelompok. Kelompok eksperimen (n=15) menggunakan pembelajaran menggunakan color card sedangkan kelompok kontrol (n=15) menggunakan pembelajaran pengkajian luka konfensional. Kami menilai keterampilan pengkajian luka sebelum dan 6 hari setelah intervensi menggunakan standard operating procedure (SOP) pengkajian luka, color card, battes jansen wound assessment form dan manikin luka infeksi. Analisa data menggunakan paired t-test dan uji N-gain score.Hasil: Hasil uji paired t-test menunjukan adanya perbedaan yang signifikan secara statistic dalam peningkatan keterampilan pada kedua kelompok (p=0.000). Namun rata-rata peningkatan (mean) menunjukan bahwa kelompok intervensi memiliki nilai perbedaan yang lebih tinggi (61.2000 menjadi 90.800) dibandingkan kelompok kontrol (59.1333 menjadi 69.9333). menggunakan media Color card mampu untuk meningkatkan keterampilan sampel hingga 76,96% dibandingkan metode konvensional yang hanya 26.08 %.Kesimpulan: Dapat disimpulkan bahwa penggunanaan media Color card efektif untuk meningkatkan keterampilan sampel dalam melakukan pengkajian luka infeksi. Kata Kunci: color card ; skill lab; laboratorium; keperawatan; perawatan luka